The Protection of Minority Shareholders within the Legal Framework: Conceptual Evidence from Turkey - BARWARI, Abdullah; SAEED, Luqman; AREE, Mustafa (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
As the equity capital has begun to surface as an essential corporate finance mechanism in emerging markets, regulations providing adequate protection for the interests of minority shareholders and investors will enable companies to access global equity capital. Turkey. as an official candidate for European Union (EU) membership, must introduce a code of corporate governance ensuring the protection of investors, particularly minority shareholders to encourage them to partake in capital markets. Consequently, this code will ease the access of Turkish companies to equity capital. Turkey has made substantial improvements in promoting the interests of shareholders and investors by focusing on the absence of an equity culture in Turkey. The application of provisions of EU capital market and company laws in Turkish law will assist in creating a legal framework for protecting minority interests. The purpose of this study is to make a contribution to the attempts to develop a corporate governance structure to protect the interests of minority shareholders and investors, which is a main requirement for developing a Turkish equity culture.